Composition Studies As A Creative Art - Bloom, Lynn (University Press of Colorado, 1998)
Bloom gathers twenty of her most recent essays (some previously unpublished) on critical issues in teaching writing. She addresses matters of philosophy and pedagogy, class and marginality and gender, and textual terror transformed to textual power. Yet the body of her work and this representative collection of it remains centered, coherent, and personal. This work focuses on the creative dynamics that arise from the interrelation of writing, teaching writing, and ways of reading-and the scholarship and administrative issues engendered by it. To regard composition studies as a creative art is to engage in a process of intellectual or aesthetic free play, and then to translate the results of this play into serious work that yet retains the freedom and playfulness of its origins. The book is fueled by a mixture of faith in the fields that compose composition studies, hope that efforts of composition teachers can make a difference, and a sense of community in its broadest meaning. Included are Bloom's well-known essays "Teaching College English as a Woman," "Freshman Composition as a Middle Class Enterprise," and many more recent works, equally provocative and insightful.